Membrane molecularly imprinted polymer for dye extraction. - Yusof, Nor Azah; Asman, Saliza (2009)

(untitled)
The present invention relates to membrane molecular imprinted polymer imprinted with Methylene Blue (MB) using MB as template molecule, methacrylic acid (MAA) as functional as synthetic method, the molecularly imprinted polymers (MIPs) particles has been synthesized and characterized. Kinetic and adsorption isotherm study has been carried out, effect of initial concentration of MB and pH effect were also invetigated. MB and two different dyes; Methylene Orange (MO) and Fast (FG) were employed for selectivity study. The results indicate that the imprinted polymers showed a good selectivity and specificity of MY dye. The molecular imprinted membrane (MIM) of MB is prepared by hybridization of MB imprinted polymer powder with polysulfone (PSf) and cellulose acetate (CA) membrane.